Distribution of 210Pb and 210Po in the Arctic water column during the 2007 sea-ice minimum: Particle export in the ice-covered basins. (December 2018) - Roca-Martí, Montserrat; Puigcorbé, Viena; Friedrich, Jana; van der Loeff, Michiel Rutgers; Rabe, Benjamin; Korhonen, Meri; Cámara-Mor, Patricia; Garcia-Orellana, Jordi; Masqué, Pere
Abstract: 210 Pb and 210 Po are naturally occurring radionuclides that are commonly used as a proxy for particle and carbon export. In this study, the distribution of the 210 Po/ 210 Pb pair was investigated in the water column of the Barents, Kara and Laptev Seas and the Nansen, Amundsen and Makarov Basins in order to understand the particle dynamics in the Arctic Ocean during the 2007 sea-ice minimum (August–September). Minimum activities of total 210 Pb and 210 Po were found in the upper and lower haloclines (approx. 60–130 m), which are partly attributed to particle scavenging over the shelves, boundary current transport and subsequent advection of the water with low 210 Pb and 210 Po activities into the central Arctic. Widespread and substantial (> 50%) deficits of 210 Po with respect to 210 Pb were detected from surface waters to 200 m on the shelves, but also in the basins. This was particularly important in the Makarov Basin where, despite very low chlorophyll-a levels, estimates of annual new primary production were three times higher than in the Eurasian Basin. In the Nansen, Amundsen and Makarov Basins, estimates of annual new primary production correlated with the deficits of 210 Po in the upper 200 m of the water column, suggesting that in situ production and subsequent export of biogenic material were the mechanisms that controlled the removal of 210 Po in the central Arctic. Unlike 210 Po, 234 Th deficits measured during the same expedition were found to be very small and not significant below 25 m in the basins (Cai et al., 2010), which indicates, given the shorter half-life of 234 Th, that particle export fluxes in the central Arctic would have been higher before July–August in 2007 than later in the season. Highlights: Largest dataset of 210 Pb and 210 Po in the Arctic Ocean to date. Minimum 210 Pb and 210 Po activities in the halocline reflect scavenging on the shelf. Potential use of the 210 Po/ 210 Pb proxy as an indicator of annual new primary production. Substantial deficits of 210 Po in surface and subsurface waters of the Makarov Basin. Higher particle export in the central Arctic before July–August in 2007.